WEB APPLICATIONS CELLULAR STYLE USING MACROMEDIA DREAMWEAVER MX 2004 - Amal Fitri; Rahayu N SKom, MM (Jurnal Sistem Informasi, 2005)
With the existence of this style mobile web site. The author hopes that the ease ofgetting information about the mobile world can be fulfilled with minimal time andcost. Society in general and mobile business people in particular can get informationabout mobile phone such as software development, applications and mobile phoneitself quick, accurate, and mobile content download service efficien. With presentedat the download page of this style mobile web a form of polyphonic ringthone andwav, screensavers and wallpapers as gif and jpeg format that can be fast, efficient,effective and efficient because users can directly download it with a very low cost,anywhere and anytime.